The last word and the word after that : - McLaren, Brian D. (Jossey-Bass, 2005)
A fable of a new kind of Christianity for a troubled world. This last volume in the trilogy that began with the award-winning A New Kind of Christian tells an intriguing fictional tale that raises urgent questions about hell–and about our view of God. What God do we believe exists? What kind of life should we live in response? How does our view of God affect the way we see and treat other people? And how does the way we see and treat other people affect our view of God? As Pastor Dan Poole and his friends and family grapple with these pressing questions, readers will find themselves moving beyond the tired rhetoric of denominational and theological categories to a view of their relationship with God that is more truly biblical, more faithful, more inspiring, more sensible, more evocative, more robust, more healing, more global, and more transforming.